Исследование возможности применения интерфейсных реле в системах гибридной коммутации обмоток бистабильных актуаторов - Клименко, Б.В.; Ересько, А.В.; Варшамова, И.С.; Лелюк, Н.А. (Електротехніка і електромеханіка, 2016)
Представлены результаты экспериментальных исследований дребезга контактов интерфейсных реле при выполнении операций их включения и отключения в нормальном режиме и в режиме ускорения срабатывания. Приводятся
рекомендации по применению малогабаритных интерфейсных реле в системах управления коммутационных аппаратов с гибридной коммутацией электрических цепей обмоток бистабильных актуаторов. Представлені результати експериментальних досліджень деренчання контактів інтерфейсних реле при виконанні
операцій їх вмикання та вимикання в нормальному режимі та в режимі прискорення спрацьовування. Наводяться
рекомендації щодо практичного застосування малогабаритних інтерфейсних реле в системах керування комутаційних апаратів з гібридною комутацією електричних кіл обмоток бістабільних актуаторів. Purpose. Development of methods of experimental determination of
action coordination characteristics of semiconductor and
mechanical switching elements in systems of hybrid commutation of
bistable actuators coils taking into account contact bounce of
mechanical switching elements. Consideration of the application
possibility of interface relay as mechanical switches, and the
definition of the duration of the intervals to ensure coordination of
the relay operation with semiconductor switches. Methodology.
Experimental determination of the time intervals between the
moments of switching transistor which controls the relay coil, and
power transistor when the switching on and off operations using a
hybrid switching device are performed; statistical processing of
experimental results. Results. The durations of the time intervals
between the moments of switching of semiconductor and
mechanical switching elements in systems of actuator coils hybrid
commutation are experimentally determined. A way of a significant
reduction of the duration of the indicated time intervals is
considered and experimentally confirmed. Originality. The scheme
of the power circuit of the control system with hybrid commutation
of the actuator coil circuit, which differs from the known schemes
that the only semiconductor switching element performs functions
of the current switching on and off, and electromechanical relay
contact elements act as a router interconnecting electrical circuits
during dead times. Practical value. The use of hybrid switches
instead of switches with semiconductor switches will significantly
reduce the cost of the actuators control system, as well as reduce
their sizes.